2004
DOI: 10.1038/sj.onc.1207815
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying differential expression of interleukin-8 in breast cancer cells

Abstract: We have recently reported that interleukin-8 (IL-8) expression was inversely correlated to estrogen receptor (ER) status and was overexpressed in invasive breast cancer cells. In the present study, we show that IL-8 overexpression in breast cancer cells involves a higher transcriptional activity of IL-8 gene promoter. Cloning of IL-8 promoter from MDA-MB-231 and MCF-7 cells expressing high and low levels of IL-8, respectively, shows the integrity of the promoter in both cell lines. Deletion and site-directed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
84
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 34 publications
10
84
0
Order By: Relevance
“…Therefore, chemotherapeutic agents with an inhibitory effect on IL-8 production may be more efficacious in treating breast cancer. MDA-MB-231 is one of the breast cancer cell lines constitutively expressing a high level of IL-8 (15,16). Consistent with previous studies (41), IL-8 enhanced the invasive ability of MDA-MB-231 cells in our experiments ( Fig.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Therefore, chemotherapeutic agents with an inhibitory effect on IL-8 production may be more efficacious in treating breast cancer. MDA-MB-231 is one of the breast cancer cell lines constitutively expressing a high level of IL-8 (15,16). Consistent with previous studies (41), IL-8 enhanced the invasive ability of MDA-MB-231 cells in our experiments ( Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Findings of recent studies have shown that the overexpression of IL-8 is associated with recurrence and poor prognosis in breast cancer (11)(12)(13)(14). The expression of IL-8 in highly metastatic breast cancer MDA-MB-231 cells is much higher than that in the non-metastatic MCF-7 breast cancer cell line (15,16). Recent studies have demonstrated that, during or after treatment, several chemotherapeutic drugs resulted in resistance and cancer metastasis associated with upregulated IL-8 in human breast cancer (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several of the identified sequence motifs appear from other studies to be functional. For example, our computational analysis revealed an AP-1 binding motif at ARE4.13 of the interleukin-8 (IL8) gene, which Freund et al (2004) showed to be important for AP-1-mediated transcriptional regulation of IL8 promoter expression. We suggest that many AREs are likely composite elements, and that regulatory cross-talk at AREs may typically modulate transcription of ARGs.…”
Section: Potential Composite Aresmentioning
confidence: 99%
“…This inhibitory cross-talk can be appreciated from the fact that an increase in both NF-kB DNA-binding activity (Nakshatri et al, 1997;Pratt et al, 2003) and expression of NF-kB target genes like IL8 (Freund et al, 2004) coincides with a shift from oestrogen dependence to oestrogen independence in breast cancer. The inverse correlation between ER and NF-kB activity is further supported by the fact that some breast tumours, resistant to the tumoricidal effect of antiestrogens, become sensitised to apoptosis and show a reduction in NF-kB activity after treatment with oestrogen (Jordan, 2004).…”
mentioning
confidence: 99%